COMMUNITY MANAGEMENT FOR COASTAL ENVIRONMENT IN MANGROVE ECOSYSTEM - Muammar Gomareuzzaman (Jurnal Ilmiah Lingkungan Kebumian, 2015)
Mangrove are typical coastal ecosystem, which has high tolerance for salinity, generally located on the coast that has amount of sediments with warm climate. Protect from waves, as well as areas affected by tides and input of freshwater and material from mainland. The objectives of research area; identify natural resources which support mangrove existence; and community participation to conserve.The research has been conduct qualitative method use deductive approach, which means of field work observation, semi-structure interview, and documentation. The main objects of the research are: (1) coastal plant, i.e. true mangrove; (2) coastal community, which give effort for coastal life and the problems.The Coastal community has been learning from previous problems that happened continuously on coastal area. They have known how to face with individual and group action plan, such as seeding mangrove plant and regularly togetherness has reforestation program both community and government.Keywords: community, coastal, mangrove ecosystem